2019 Update to the American College of Clinical Pharmacy Pharmacotherapy Didactic Curriculum Toolkit. Issue 2 (5th November 2019) - Flannery, Alexander H.; Soric, Mate M.; Benavides, Sandra; Bobbitt, Laura J.; Chan, Alexandre; Crannage, Andrew J.; Flores, Emily K.; Gibson, Caitlin M.; Gurgle, Holly E.; Kolanczyk, Denise M.; Merlo, Jessica R.; Schwinghammer, Terry L.
Abstract: Introduction: The American College of Clinical Pharmacy (ACCP) Pharmacotherapy Didactic Curriculum Toolkit was created by the 2008 ACCP Educational Affairs Committee to provide guidance to schools and colleges of pharmacy for didactic pharmacotherapy curricular development. The toolkit was revised and updated by the 2016 ACCP Educational Affairs Committee. Objectives: In accordance with the ACCP Board of Regents decision to update the toolkit every 3 years, the 2019 ACCP Publications Committee was charged with updating the 2016 toolkit to guide adequate disease state inclusion and depth of pharmacotherapy coverage in pharmacy curricula. Methods: The committee retained the competency‐based tier definitions and organization of the 2016 toolkit. Multiple literature resources were reviewed to assess medical conditions responsive to drug therapy for inclusion in the 2019 toolkit. The committee also reviewed the tier designation for all toolkit entries for appropriateness, given recent advances in medical care and evolving patient care responsibilities of clinical pharmacists. Updates to the toolkit were made by consensus with electronic voting when required. Results: The 2019 toolkit contains 302 topics, including 94 (31%) tier 1, 133 (44%) tier 2, and 75 (25%) tier 3 entries. There are 26 additional topics in the updated toolkit, including 12 new tier 1 topics that are generally treated with nonprescription medications. Eleven new topics were added to tier 2, and 20 topics were added to tier 3 (including 11 topics in the Oncologic Disorders section). The tier classification of some conditions was changed to reflect current pharmacy practice expectations. Conclusion: As with the 2016 toolkit, the large number of tier 1 topics will require schools and colleges to employ creative teaching strategies to achieve practice competence in all graduates. The large number of tier 2 topics highlights the importance of postgraduate training and experience for pharmacy graduates desiring to provide direct patient care.